Strategi Pembelajaran PAI untuk Meningkatkan Mutu Pendidikan dan Karakter Peserta Didik - Muhammad Hasan Bashri; Hamdani Hamdani; Abd. Mu'is (Journal of Humanities, Social Sciences, and Education, 2025)
Islamic Religious Education (PAI) plays a strategic role in shaping the spiritual, moral, and social abilities of students in the digital era. However, technological developments, globalization, and cultural changes present new challenges to the learning process. This study aims to analyze the relevance of innovative, effective, and appropriate PAI learning strategies for the needs of 21st-century students. The method used is a literature review, reviewing various recent sources related to the implementation of PAI learning strategies in schools. The results of the study indicate that project-based learning strategies, exemplary approaches, contextual learning, and digital technology integration can improve the quality of learning and help internalize Islamic values ​​more meaningfully. In addition, the use of digital media such as animated videos, Islamic comics, prayer simulations, and online learning platforms can increase student interest in learning and active participation. However, the implementation of innovative learning strategies still faces obstacles, including uneven teacher competency, limited digital resources, and suboptimal learning environment support. Therefore, ongoing teacher training, collaboration between schools and families, and the development of learning media tailored to student needs are needed. This research confirms that the implementation of holistic, creative, and adaptive Islamic Religious Education (PAI) learning strategies has great potential in developing students who are faithful, have noble character, and are able to face the challenges of the times.